Research Trends of Creative Thinking in Education: Bibliometric Analysis 2016–2025 - F. Shoufika Hilyana; Dwi Yulianti; Ani Rusilowati; Bambang Subali (Jurnal Pemberdayaan Masyarakat, 2026)
Creative thinking is an essential skill of the 21st century, seen as essential for the development of individuals, society, and the global workforce. This study aims to map the research landscape of creative thinking in education during the period 2016–2025 through a data-based bibliometric analysis of Scopus data. By applying the keywords "creative thinking" and "students", 1,340 documents were analyzed using a combination of Scopus, VOSviewer, and Biblioshiny to identify publication trends, document type distribution, dominant keywords, and thematic evolution. The study's results show significant growth in publications since 2016, with a peak from 2020 to 2024. Journal articles dominated (883), followed by conference papers (550), with an international collaboration rate of 10.68%. The thematic analysis revealed two main clusters: the conceptual-pedagogical approach, which emphasizes learning theory and strategies, and the empirical-evaluative approach, which focuses on measuring creative thinking skills. Trends toward integrating digital technology, STEM/STEAM-based learning, and artificial intelligence (AI) to support creative thinking skills. The results of the study are expected to provide a basis for education policy, pedagogical innovation, and future research directions.